2011
DOI: 10.1590/s0102-311x2011001300010
|View full text |Cite
|
Sign up to set email alerts
|

Improving survival in children with AIDS in Brazil: results of the second national study, 1999-2002

Abstract: The objective of this study is to characterize survival in children with AIDS diagnosed in Brazil between 1999-2002, compared with the first national study (1983-1998). This national retrospective cohort study examined a representative sample of Brazilian children exposed to HIV from mother-to-child transmission and followed through 2007. The survival probability after 60 months was analyzed by sex, year of birth and death, clinical classification, use of antiretroviral therapy (ART) and prophylaxis for opport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 34 publications
(51 reference statements)
0
22
0
4
Order By: Relevance
“…The present study has limitations beyond those already identified and described extensively in our previous publications on the topic [14-17]. Children in both cohorts had differing criteria for AIDS case definition, with greater sensitivity in the last one [6].…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The present study has limitations beyond those already identified and described extensively in our previous publications on the topic [14-17]. Children in both cohorts had differing criteria for AIDS case definition, with greater sensitivity in the last one [6].…”
Section: Discussionmentioning
confidence: 91%
“…Thus, they had the chance to be treated with ARV, even in advanced stages of HIV infection [6,13,14]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations